The effect of psychoeducation on the social skills and problem-solving skills of female prisoners - KARACA, SEMRA (My University, 2022)
Objectives: This research was designed to evaluate the effect of education developed to address the psychosocial needs of women in penal institutions related to social skills and problem-solving skills. Methods: The research was conducted between April 2013 and March 2014 with women serving a sentence in 2 Type E, closed prisons in Aydın, Turkey. The data were collected using a personal information form, a brief questionnaire, the Social Skills Inventory (SSI), the Problem-Solving Inventory (PSI) and an evaluation form. Content analysis was used to assess qualitative data, including frequency and percentage distribution, and quantitative data were evaluated using a t-test for dependent groups. Results: The average age of the participants was 37.79±8.94 years, and 48.1% were illiterate. In all, 25.9% of the women were convicted of theft and 72.2% had another 1-4 years remaining to serve. The mean PSI score before the psychoeducation course was 115.72±15.77, and 110.85±14.01 after the program. The mean SSI score was 243.94±31.15 before the psychoeducation course and 248.92±42.59 afterwards. There was a statistically significant difference between the mean scores of both scales before and after the psychoeducation program. Conclusion: The psychoeducation program prepared to meet the needs of the female prisoners studied had a positive effect on their social skills and problem-solving skills. The addition of psychoeducation programs to the educational programs offered in penal institutions could be very beneficial. Additional studies with control group monitoring are recommended.
Keywords: Sağlık Bilimleri; Health Sciences; Psikiyatri; Klinik Tıp (MED); PSYCHIATRY; Clinical Medicine (MED); Psikiyatrik Ruh Sağlığı; Psikiyatri ve Ruh Sağlığı; Psychiatric Mental Health; Psychiatry and Mental Health; Female prisoners; problem-solving; psychiatric nursing; psychoeducation; social skills; Female prisoners; problem-solving; psychiatric nursing; psychoeducation; social skills